Automatic detection of facial expressions during the Cyberball paradigm in Borderline Personality Disorder: a pilot study - Arango-de-Montis, Iván; Reyes-Soto, Adriana; Rosales-Lagarde, Alejandra; Eraña-Díaz, Marta-Lilia; Vázquez-Mendoza, Enrique; Rodríguez-Delgado, Andrés; Muñoz-Delgado, Jairo; Vázquez-Mendoza, Isaac; Rodriguez-Torres, Erika Elizabeth (Frontiers in Psychiatry, 2024)
Borderline Personality Disorder (BPD) symptoms include inappropriate control of anger and severe emotional dysregulation after rejection in daily life. Nevertheless, when using the Cyberball paradigm, a tossing game to simulate social exclusion, the seven basic emotions (happiness, sadness, anger, surprise, fear, disgust, and contempt) have not been exhaustively tracked out. redIt was hypothesized that these patients would show anger, contempt, and disgust during the condition of exclusion versus the condition of inclusion. When facial emotions are automatically detected by Artificial Intelligence, ``blending'', -or a mixture of at least two emotions- and ``masking'', -or showing happiness while expressing negative emotions- may be most easily traced redexpecting higher percentages during exclusion rather than inclusion. redTherefore, face videos of fourteen patients diagnosed with BPD (26±6 years old), recorded while playing the tossing game, were analyzed by the FaceReader software. The comparison of conditions highlighted an interaction for anger: it increased during inclusion and decreased during exclusion. During exclusion, the masking of surprise; i.e., displaying happiness while feeling surprised, was significantly more expressed. Furthermore, disgust and contempt were inversely correlated with greater difficulties in emotion regulation and symptomatology, respectively. Therefore, the automatic detection of emotional expressions during both conditions could be useful in rendering diagnostic guidelines in clinical scenarios.